Complement Hopfian Module - Sufyan A. Hamid; Nada K. Abdullah (Tikrit Journal of Pure Science)
Amodule M is called comp. Hopfian if any epomorphism f  End (M) . ker f is complement of N in M for some submodule N of M . In this study, some properties of comp. Hopfian modules are investigated with examples .